Smart Robotic Exoskeleton: Constructing Using 3D Printer Technique for Ankle-Foot Rehabilitation - Salih, Rafal Khalid; Aboud, Wajdi Sadik (Universitas Muhammadiyah Yogyakarta, 2023)
Patients with spinal cord injury (SCI), stroke, and coronavirus patients must undergo a rehabilitation process involving programmed exercises to regain their ability to perform activities of daily living (ADL). This study focuses on the rehabilitation of the foot-ankle joint to restore ADL through the design and implementation of a rehabilitation exoskeleton with three degrees of freedom (abduction/adduction, inversion/eversion, and plantarflexion/dorsiflexion movements). increase the patients cause worker fatigue, emotional exhaustion, a lack of motivation, and feelings of frustration, all contributing to a decrease in work efficacy and productivity. The robotic exoskeleton was developed to overcome this limitation and support the medical rehabilitation section. The main goal of this study is to develop a portable exoskeleton that is comfortable, lightweight, and has a range of motion (ROM) compatible with human anatomy to ensure that movements outside of this range are minimized, the anthropometric parameters of a typical human lower foot have been considered. In addition, it's a home-based rehabilitation device which means the exoskeleton can be used in any environment due to its lightweight and small size to accelerate the rehabilitation process and increase patient comfort. The proposed autonomous exoskeleton structure is designed in Solid Works and constructed with polylactic acid (PLA) plastic, the reason PLA was chosen is its lightweight, available, stiff material, and low cost, using 3D printing technology the exoskeleton was manufacturing. Electromyography (EMG) and angle data were extracted using EMG MyoWare and gyroscope sensors, respectively, to control the exoskeleton. It was evaluated on its own then with 2 normal subjects and 17 patients with stroke, spinal cord injury (SCI), and coronavirus. The limitation that has been faced was that the sessions were limited due to the limited time provided for the study. According to the improvement rate, the exoskeleton has a significant impact on regaining muscle activity and improving the range of motion of foot-ankle joints for the three types of patients. The rate of improvement was 300%, 94%, and 133.3% for coronavirus, SCI, and stoke respectively. These results demonstrate that this exoskeleton can be utilized for physiotherapy exercises.